Teachers' Perceptions of Continuous Professional Development in Innovative Mathematics and Science Teaching - Onesme Niyibizi; Marie Claudine Uwitatse; Vedaste Mutarutinya (Journal of Instructional Mathematics, 2024)
This qualitative study investigated teachers' perceptions of the Continuous Professional Development Certificate in Innovative Teaching of Mathematics and Science (CPD ITMS) in a selected public secondary school in Rwanda. The program was introduced to address longstanding challenges in STEM education, including outdated pedagogical practices, limited teacher training, and poor student engagement in mathematics and science subjects. Prior to the implementation of CPD ITMS, many teachers lacked the necessary skills to adopt innovative teaching methods, which negatively impacted student performance in STEM disciplines. Through interviews with four teachers, this study revealed that CPD ITMS positively influenced pedagogical skills and student outcomes by promoting more interactive and student-centered learning techniques. These improvements directly addressed the initial gaps in teacher preparation and student engagement, offering promising solutions to the challenges facing STEM education in Rwanda. However, the study also identified ongoing barriers such as time constraints and resource limitations, which delay the full implementation of the program. The findings emphasized the need for sustained school support and targeted policy reforms to enhance the effectiveness of CPD ITMS, thereby advancing STEM education. Addressing these challenges through clear policy directives and resource allocation is critical for future progress.